2021
DOI: 10.3390/f12030350
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes in Tree Rings of Pinus heldreichii Can Indicate Climate Variability over the Eastern Mediterranean Region

Abstract: A long-term context is important for understanding past climatic variability. Although tree-ring widths (TRWs) are widely used as a proxy for reconstructing past climate, the use of annually-resolved values of δ13C and δ18O tree-ring stable isotopes (TRSIs) is increasing and may provide further valuable information. Here, we present a 487-year-long TRW chronology and 240-year-long TRSI chronology for Bosnian pine (Pinus heldreichii H. Christ) and compare them to each other. We demonstrate that both δ13C and δ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
1
2
0
1
Order By: Relevance
“…The first-differenced data for δ 18 O shows tendencies toward a common signal, which suggests that the trees are sensitive to a common environmental factor(s), e.g., drought. The range of δ 18 O in the present study (29.2-36.3‰) is consistent with that recorded for trees in semi-arid regions (Xu et al 2011;Qin et al 2015) or in the subtropical belt of the Eastern Mediterranean (Lukač et al 2021). It indicates uptake of enriched water sources or high isotopic enrichment of δ 18 O leaf water caused by high transpiration rates and subsequent assimilation (Sarris et al 2013;Treydte et al 2014).…”
Section: Coping Strategy Of M Peregrina Under Drought Conditionssupporting
confidence: 90%
“…The first-differenced data for δ 18 O shows tendencies toward a common signal, which suggests that the trees are sensitive to a common environmental factor(s), e.g., drought. The range of δ 18 O in the present study (29.2-36.3‰) is consistent with that recorded for trees in semi-arid regions (Xu et al 2011;Qin et al 2015) or in the subtropical belt of the Eastern Mediterranean (Lukač et al 2021). It indicates uptake of enriched water sources or high isotopic enrichment of δ 18 O leaf water caused by high transpiration rates and subsequent assimilation (Sarris et al 2013;Treydte et al 2014).…”
Section: Coping Strategy Of M Peregrina Under Drought Conditionssupporting
confidence: 90%
“…This difference may be because, in this study, we used the whole wood cellulose from black pine (Pinus nigra) trees, which would contain the climate signal recorded during the early growing season, whereas other studies used latewood cellulose from oak trees (Quercus robur) 20,30 . A negative relationship between our pine δ 18 O and spring-summer precipitation has been found in the adjacent regions of Montenegro, Bosnia, and Herzegovina 32 .…”
Section: Resultsmentioning
confidence: 56%
“…Nowadays, various studies demonstrated strong species-specific sensitivity to environmental drivers evaluated through tree ring stable isotopes [21,22]. The tree rings stable carbon isotopes are widely used to retrospect trees response to climate change due to carbon dioxide increase.…”
Section: Introductionmentioning
confidence: 99%